Life and Humor According to Seinfeld: Sociocultural Aspects of a Classic Sitcom in the US and Beyond - Lénárt, András (AMERICANA E-journal of American Studies in Hungary, 2023)
In the late 1980s, Jerry Seinfeld and Larry David came up with the idea for a situation comedy that became a true classic of American television and is still a reference point for comedies today. The 80s and 90s brought the golden age of sitcoms, with Seinfeld becoming one of the most important TV shows in the United States. The series became an undeniable landmark of American popular culture, considered by many to be one of the greatest and most influential sitcoms of all time. It also became the best representative of observational comedy, with the concerns, reactions, minor existential crises and life situations of the four main characters familiar to the large public. At the same time, the negative remarks were also present depicting this show that is basically about nothing and one that tries to captivate the audience with excessive simplicity. In the United States, the show achieved cult status, which it still retains, but it has been less popular in other countries due to some of the everyday problems presented in the episodes not necessarily unique to US society and culture. The aim of my article is to show the sociocultural aspects that turned Seinfeld into a milestone and also to describe what characterizes the Seinfeldian version of observational humor by focusing on the reasons for the sometimes extreme reactions (both positive and negative) to this type of humor in the US and beyond.